Research on Path Planning Method of Indoor Mobile Robot based on Improved A-Star Algorithm - Fu, Yaoyao; Guan, Ziyu; Yuan, Wenlong (2022 10th International Conference on Information Systems and Computing Technology (ISCTech), 2022)
Aiming at the problems of high complexity, large positioning error and difficulty in adapting to dynamic environment of indoor mobile robot path planning algorithm, in this paper, we propose an improved indoor mobile path planning scheme based on A-Star algorithm. By setting the heuristic function, the target tendency of the algorithm iteration is enhanced, and the RTT algorithm feature is introduced to quickly generate path nodes, to optimize the rapid planning ability of the overall device for the dynamic environment and reduce the local optimization of the planning results and wasted hash power. After Xpresso's simulation test, the improved A-S tar algorithm has stronger path solving ability and higher positioning accuracy, and the robot path is smoother.